The affective dimension of crisis subjects: Teaching environmental communication through intersecting crisis - Tania Leimbach; Jennifer Kent; Jeremy Walker (Australian journal of adult learning, 2022)
Confronting the existential threat of climate and ecological crises in undergraduate teaching presents complex challenges. Educators in environmental and climate change studies rightly communicate the scale and urgency of these unfolding crises, yet at times fail to take into account the emotional and mental health impacts upon students acquiring this knowledge. This article examines the affective dimensions of learning in 'crisis subjects'. It draws insights from case study research on the experience of Australian university teachers and students in a subject called Environmental Communication, delivered during a period of intersecting crises: climate-change driven drought, catastrophic bushfires, and the emergence of Covid-19. The psychoanalytic concept of 'difficult knowledge' (Britzman, 1998; 2004) is taken up to shed light on the inherent challenges of teaching and learning in this context. Many students in the study were deeply affected by their learning experience, and recognise its importance, but also struggle to integrate it with anticipated future roles. The authors argue that students and educators need new knowledge, capacities and resources to address the affective dimension of teaching and learning and to grapple with the collective social trauma of the climate crisis.